ANALISIS VARIAN DUA FAKTOR DALAM RANCANGAN PENGAMATAN BERULANG ( REPEATED MEASURES ) - Alif Hartati; Triastuti Wuryandari; Yuciana Wilandari (Jurnal Gaussian, 2013)
The experimental design is a series of tests, both using descriptive statistics and inferential statistics that aims to transform the input variables into an output which is the response of the experiment. In one study, the response sometimes observed in every experiment performed more than once at different times during the study called with Repeated Measures. Observation time as if viewed as an additional factor, resulting in a repeated measures seen as a two-factor design with split-plot patterns. Factors that attempted allocated as main plots and allocated observation time as a subplot. Step-by-step analysis to test the normality of the error, test the homogeneity of variance, determine the degrees of freedom, sum of squares and mean squares of each factor. The next hypothesis to test for factor a, factor b and interaction affect both whether the observed response. If any effect, it is necessary to further test the Duncan test. The data used are secondary data on the effect of temperature, time of observation and interaction both the amylase enzyme produced by the bacterium bacillus subtilis. Results obtained by the analysis of temperature, time of observation and interaction both significantly influence the observed response.